Iklim Komunikasi Organisasi Badan Kemakmuran Masjid (BKM) Al-Hikmah Di Desa Kelurahan Bandar Selamat Pada Masa Pandemi Covid-19 - Lubis, Siti Suailah; Harahap, Nursapiah; Susanti, Neila (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Coronaviruss disease or Covid-19 has changed the whole order of life including places of worship, especially for Muslims. To reduce the rate of spread of the virus, various routine activities normally carried out by the BKM A-IHikmah organization must be closed and stopped even for a while. In addition, communication within the BKM Al-Hikmah organization must also be limited due to the Covid-19 pandemic as in the BKM organization in the Bandar Selamat sub-district, one of which is BKM Al-Hikmah. The purpose of this study was to find out how the organizational communication climate of the Al-Hikmah Mosque Prosperity Board in Bandar Selamat Village was during the Covid-19 Pandemic. This research is a qualitative research with a descriptive design. Data collection methods used in this study were interviews and observation. The informants in this study were the Chairperson of the Al-Hikmah Mosque Prosperity Agency (BKM) and the BKM Al-Hikmah Dakwah Coordinator.The results of this study are the communication climate that occurs in the Al-Hikmah Mosque Kenaziran Board (BKM) organization in Bandar Selamat Village during the Covid-19 Pandemic Period as seen from the five values ​​in the communication climate such as the value of support, the value of participation in decision making, the value of trust, openness , and candor, as well as the value of high work goals.The communication climate of the BKM Al-Hikmah organization during the Covid-19 pandemic was a good climate and felt constructive by members of the organization because of mutual respect, motivation and encouragement for members of the organization to be even better. The existence of a good communication climate will make members of the organization form good interactions among members of the organization.